Flexible Na/K‐Ion Full Batteries from the Renewable Cotton Cloth–Derived Stable, Low‐Cost, and Binder‐Free Anode and Cathode. Issue 38 (27th August 2019) - Guo, Jin‐Zhi; Gu, Zhen‐Yi; Zhao, Xin‐Xin; Wang, Mei‐Yi; Yang, Xu; Yang, Yang; Li, Wen‐Hao; Wu, Xing‐Long
Abstract : Flexible Na/K‐ion batteries (NIBs/KIBs) exhibit great potential applications and have drawn much attention due to the continuous development of flexible electronics. However, there are still many huge challenges, mainly the design and construction of flexible electrodes (cathode and anode) with outstanding electrochemical properties. In this work, a unique approach to prepare flexible electrode is proposed by utilizing the commercially available cotton cloth–derived carbon cloth (CC) as a flexible anode and the substrate of a cathode. The binder‐free, self‐supporting, and flexible cathodes (FCC@N/KPB) are prepared by growing Prussian blue microcubes on the flexible CC (FCC). Na/K‐ion full batteries (FCC//FCC@N/KPB) are assembled by using FCC and FCC@N/KPB as anode and cathode, respectively. Electrochemical performance, mechanical flexibility, and practicability of FCC//FCC@N/KPB Na/K‐ion full batteries are evaluated in both coin cells and flexible pouch cells, demonstrating their superior energy‐storage properties (excellent rate performance and cycling stability) and remarkable flexibility (they can work under different bending states). This work provides a new and profound strategy to design flexible electrodes, promoting the development of flexible NIBs/KIBs to be practical and sustainable. Abstract : Flexible Na/K‐ion full batteries with promising energy‐storage performance and remarkable flexibility are assembled by utilizing the commercially available cotton cloth–derived carbon cloth as flexible anode and cathode substrate. The flexible cathodes are prepared by growing Prussian blue microcubes on the flexible substrate. Electrochemical performance, flexibility, and practicability of batteries are evaluated in both coin cells and flexible pouch cells.